2015
DOI: 10.1039/c5ra19115g
|View full text |Cite|
|
Sign up to set email alerts
|

Folate appended chitosan nanoparticles augment the stability, bioavailability and efficacy of insulin in diabetic rats following oral administration

Abstract: The present study embarks upon the folic acid (FA) functionalization of chitosan nanoparticles and its implications on stability, oral bioavailability and hypoglycemic activity following oral administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Formulated nanoparticles demonstrated the persistent release of insulin up to 24 h. Encapsulated insulin remained stable both conformationally and chemically. Uptake studies in Caco-2 cell lines deduced remarkably higher effects, so was the bioavailability through oral administration [ 108 ]. Chitosan-EDTA coated (CEC) liposomes encapsulating insulin were synthesized by reverse-phase evaporation method and the shape obtained was either spherical or ellipsoidal.…”
Section: Introductionmentioning
confidence: 99%
“…Formulated nanoparticles demonstrated the persistent release of insulin up to 24 h. Encapsulated insulin remained stable both conformationally and chemically. Uptake studies in Caco-2 cell lines deduced remarkably higher effects, so was the bioavailability through oral administration [ 108 ]. Chitosan-EDTA coated (CEC) liposomes encapsulating insulin were synthesized by reverse-phase evaporation method and the shape obtained was either spherical or ellipsoidal.…”
Section: Introductionmentioning
confidence: 99%
“…Ligands used for uptake include; vit-amin B 12 , biotin and folate [190]. Researchers have used folate coupled chitosan nanoparticles to further increase the uptake of peptides [191]. Folic acid is actively absorbed in the GI tract by a proton-coupled FA transporter.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…in vitro studies showed a statistically significant improvement in insulin delivery using folate linked nanoparticles, compared to free insulin and chitosan nanoparticles. When these formulations were given to diabetic rats orally, the folate linked nanoparticles resulted in a more sustained decrease in blood glucose compared to compared to free insulin and chitosan nanoparticles [191].…”
Section: Nanoparticlesmentioning
confidence: 99%
“…Oral administration of nanoparticles improves bioavailability and hypoglycemia in comparison with insulin solution administered subcutaneously. [6][7][8] In addition, a large proportion of drugs (about 40%) are poorly soluble. Subsequently, the enhancement of their oral bioavailability is the most important challenge in their development.…”
Section: Introductionmentioning
confidence: 99%